Exit eaudiobook - Bauer, Belinda (Dreamscape Media, 2021)
Felix Pink is retired. Widowed for more than a decade and a painfully literal thinker, he has led a life of routine and is, not unhappily, waiting to die a hopefully boring death. He occupies himself volunteering as an Exiteer-someone who sits with terminally ill people as they die by suicide, assisting with logistics and lending moral support, then removing the evidence so that family and friends are not implicated in the death. When Felix lets himself into Number 3 Black Lane, he's there to perform an act of kindness and charity: to keep a dying man company as he takes his final breath. But just fifteen minutes later, Felix is on the run from the police-after making the biggest mistake of his life. Now his routine world is turned upside down as he tries to discover whether what went wrong was a simple mistake-or deliberate, a murder. With a novel that is part murder mystery, part coming-of-old-age story-however short that future may be—Belinda Bauer continues to redefine the boundaries of crime fiction. With the compassion and dark humor of Jonas Jonasson and the twisted thriller plotting of Rear Window, Exit is a novel listeners will not soon forget.